Modelling Zakat and Waqf Scheme for Empowering Across-the-board Refugees - Herman, Sebastian; Wahyudi Indrawan, Imam (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
The objective of this study is to propose a model of empowering global refugees by utilizing zakat and waqf through Islamic microfinance institutions. The model introduced is an extended model of the model developed by Kachkar (2017) and Indrawan et al. (2018). A thorough review of relevant literature is conducted to develop this model. The proposed approach, referred to as the Integrated Zakat and Waqf Model for Refugees (IZWMR), introduces the zakat element as an extension of the previous model. Additionally, the waqf component of the model includes not only cash waqf but also land waqf, thereby enabling the optimal utilization of idle waqf assets to empower refugees and support their livelihood. This study aims to raise awareness within society about the challenges faced by refugees, provide a comprehensive model to address the global refugee crisis, and create opportunities for the more effective and impactful utilization of Islamic social finance instruments, such as zakat and waqf.